The Application of Islamic Architecture in the Floor Plan Design of Livable Houses in Banda Aceh - Idawati, Dyah Erti; Maharani, Lisa; Kh, Fithria Zahwa (Rumoh Journal of Architecture, 2025)
The livable housing program is one of the poverty alleviation efforts carried out by the Banda Aceh City Government. The implementation of livable houses has been carried out since 2008 until now. Livable houses built by the Banda Aceh city government used floor plans based on Indonesian National Standards (SNI). On the other hand, the city of Banda Aceh is the only city that implements Islamic Sharia, which should be applied in various aspects of people's lives, including their houses. A house as the smallest unit of the family should be a model for learning and implementing Islamic Sharia, including a livable house. Therefore, the aim of this research is to identify the application of Islamic architecture in design prototypes of livable house plans and analyze three case studies of livable houses in the city of Banda Aceh. The results of the analysis are then used as considerations in proposing design recommendations that are in accordance with Islamic Architecture criteria. The research method used is descriptive qualitative research, with data collection techniques in the form of observation, interviews and secondary data in the form of documents related to livable houses from the Banda Aceh City Public Housing and Settlement Area Service. Three livable houses in Banda Aceh built over five year period were selected to see post-occupancy implementation. Based on the seven criteria for an Islamic house, the results of the research state that (1) The current prototype of a livable house plan does not meet all the design criteria for Islamic architecture (2) After occupancy the placement of furniture and use of space also does not meet all the criteria for an Islamic house, however, residents are trying to arrange the houses with minimal use of furniture so that its function is more flexible (3) Two recommendations for layouts of a livable house type 36-38 are proposed that meet the criteria for Islamic architecture.